2016
DOI: 10.1186/s13071-016-1598-y
|View full text |Cite|
|
Sign up to set email alerts
|

Leishmania infantum-specific production of IFN-γ and IL-10 in stimulated blood from dogs with clinical leishmaniosis

Abstract: BackgroundThere is limited information available on cytokine profiles in dogs with different degrees of disease severity due to natural infection of Leishmania infantum. The aim of this study was to investigate L. infantum-specific IFN-γ and IL-10 production in blood from dogs with leishmaniosis at diagnosis and correlate these findings with disease severity, humoral immune response and blood parasitemia.MethodsSixty dogs were diagnosed based on physical examination, routine laboratory tests, L. infantum-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(109 citation statements)
references
References 47 publications
12
96
0
1
Order By: Relevance
“…Slight modifications were done for the IFN-γ ELISA as described elsewhere [27]. Standard curve for TNF-α started with 1000 pg/ml and two-fold dilutions were made until 7.8 pg/ml concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Slight modifications were done for the IFN-γ ELISA as described elsewhere [27]. Standard curve for TNF-α started with 1000 pg/ml and two-fold dilutions were made until 7.8 pg/ml concentration.…”
Section: Methodsmentioning
confidence: 99%
“…It has been accepted that susceptibility is associated with an exacerbated humoral immune response (Th2) and a reduced cellular immune response (Th1) (Alvar et al, 2004;Baneth et al, 2008). Increased production of IL-10, a major Th2 cytokine, is associated with progression of the canine infection (Boggiatto et al, 2010), while higher expression of IFN-gamma, a Th1 cytokine, is correlated with a lower blood parasite load (Solano-Gallego et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We attempted to ascertain the involvement of the Th1 cytokine TNF‐alpha and the Th2 cytokine IL‐10 and observed that infection of macrophages from healthy dogs with promastigotes of L. infantum elicited IL‐10 production in the supernatant of 3‐day‐cultured macrophages. Higher IL‐10 correlated with increased parasite load and severity of visceral leishmaniasis in dogs caused by L. infantum , although some studies have suggested that IL‐10 is not associated with disease susceptibility in dogs . However, the association between increased HO‐1 levels and increased IL‐10 levels in infected dogs has been previously addressed, and this could also be a mechanism responsible for the susceptibility of this species.…”
Section: Discussionmentioning
confidence: 98%
“…Higher IL-10 correlated with increased parasite load and severity of visceral leishmaniasis in dogs caused by L. infantum, 26 although some studies have suggested that IL-10 is not associated with disease susceptibility in dogs. 33 However, the association between increased HO-1 levels and increased IL-10 levels in infected dogs has been previously addressed, 10 and this could also be a mechanism responsible for the susceptibility of this species. Additionally, it is already known that IL-10 induces expression of HO-1 via a p38 mitogenactivated protein kinase-dependent pathway and that inhibition of HO-1 protein synthesis or activity significantly reverses the inhibitory effect of IL-10.…”
Section: And In Both Mousementioning
confidence: 99%